Qualitative research on sport and physical culture - Young, Kevin, 1959-; Atkinson, Michael, 1971- (Research in the sociology of sport ;, 2012)
This volume takes a fresh approach to qualitative research on sport and physical culture by presenting "student friendly" engaging chapters that clearly articulate the significance and practice of qualitative and/or critical methods in plain and convincing language. It outlines contemporary, cutting-edge approaches in qualitative research methods that students in undergraduate programs in sociology and sociology of sport, as well as, for instance, sport, exercise, kinesiology, or health, can understand clearly. Chapters revolve around one principal method in qualitative methodology, and look at why certain methodological choices were made, what problems were faced, and how these were overcome. Classic issues in methodology, contemporary issues in research methods and innovative trends in qualitative research are addressed through case study examples from emerging and exciting areas of research in sport studies. Topics covered include: historical methods; ethnography; auto-ethnography; embodied methods; interviewing; narratives; participatory action methods; interpretative phenomenological analysis; media analysis; and visual methods.